Analisis Perawatan Gate Valve Dengan Metode Reliability Centered Maintenance (RCM) Di PT. Valvindo Mitra Raya - Agus Syahabuddin; Adi Candra; Muhammad Syaiful Habidin (Universitas Pamulang, 2021)
Competition in the industry is getting tougher, and companies are required to make improvements in various departments, one of which is the maintenance department which supports system operations so that they run as desired. PT. Valvindo Mitra Raya which is engaged in Water Pipe Installation and Machanical Repair/Reconditioning. Until now, preventive maintenance activities are scheduled every year, but the maintenance department still carries out many corrective maintenance activities. This final project aims to determine the optimal maintenance action and determine maintenance intervals on the Gate Valve machine. In order to achieve the goal of writing, perform a detailed analysis using the Reliability Centered Maintenance (RCM) method, where the initial application is to find out the functions and damage that can occur in a system, starting from the sub-system to the component level, FMEA table for determining critical components, for determine the direct or indirect impact with Intermediate Decision (IDT) analysis, and then to determine the optimal maintenance task through Logic Tree Analysis (LTA). The results obtained are in the form of problem solving, namely the company performs machine maintenance intervals on Disc components with maintenance intervals of 224.39 hours or 32 working days, with the aim of knowing the level of component damage by carrying out Condition Monitoring actions, to overcome unpredictable failures by performing Corrective Maintenance actions and to overcome failures that are affected by the age of components, scheduled replacement actions.